Efeito do implante coclear unilateral e bilateral simultâneo no zumbido: um estudo prospectivo - Santos, Mariana Batista de Souza; Tenório, Jacqueline Pimentel; Lima, Karine Maria do Nascimento; Almeida, Grazielly de Farias; Andrade, Kelly Cristina Lira de (Distúrbios da Comunicação, 2017)
Van Zon A et al. Effect of unilateral and simultaneous bilateral cochlear implantation on tinnitus: A Prospective Study. Laryngoscope. Apr, 2016; 126(4):956-61.